PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PASAR PERUSAHAAN YANG DIMEDIASI OLEH PENGUNGKAPAN LAPORAN KEBERLANJUTAN - Stefanie Salim; Megawati Oktorina (Optimum: Jurnal Ekonomi dan Pembangunan, 2016)
This study aimed to analyze the infl uence of the Good Corporate Governance (GCG) on the market performance that is mediated by the disclosure of sustainability report. This study used two model which fi rst model aims to obtain empirical evidence about the infl uence of GCG and the disclosure of sustainability reporting on market performance. The second model aimed to get empirical evidence whether disclosure ofthe sustainability report is able to mediate the relationship between GCG and market performance.This study uses multiple linear regression model to test the hypothesis in the fi rst and second research model. The sample in this study is a non-fi nancial company participant Indonesia Sustainability Report Awards (ISRA) 2009-2012 listed in the Indonesia Stock Exchange. In the fi rst research model using 30 samples, while the second models using 29 samples.The results showed that the GCG as measured by the number of meetings of the board of directors and the proportion of independent board have a signifi cant effect on the market performance. However, GCG as measured by governance committee did not prove the existence of an effect on the market performance. In addition, the disclosure of sustainability reports proved positive signifi cant effect on the market performance.The results also found that disclosure of the sustainability report is able to mediate the relationship between GCG and market performance.